Extracellular Matrix-Remodeling Enzymes as Targets for Natural Antiangiogenic Compounds - Carrillo, Paloma; García-Caballero, Melissa; Bernal, Manuel; Manrique-Poyato, María Inmaculada; Martínez-Póveda, Beatriz Amparo; Rodríguez-Quesada, Ana María; Medina-Torres, Miguel Ángel (Springer Nature Switzerland, 2022)
Angiogenesis, or new blood vessels formation, comprises a series of tight regulated and coordinated steps guided by the balance between proangiogenic and antiangiogenic signals. Although physiological angiogenesis occurs in some context such as embryogenesis or wound healing, it is a very restricted process in adults, therefore, it is associated to several pathologies as cancer, arthritis or age- related macular degeneration. For this purpose, plenty of compounds from natural sources have been studied and their antiangiogenic potential has been demonstrated. Most of them are isolated from plants, such as the major catechin found in green tea epigallocatechin-3-gallate (EGCG) or the isoflavonoid genistein. Nevertheless, compounds with antiangiogenic potential can be found in several species of animals, fungi, algae or bacteria, for instance, aeroplysinin-1, AD0157, carrageenan derivates and rapamycin, respectively. The extracellular matrix (ECM) remodeling plays a key role in the formation of new blood vessels. The degradation of the ECM components not only provides a structural scaffold for the nascent vessels, but it is also strongly involved in endothelial cell signaling, promoting or inhibiting this complex process. In this regard, targeting the ECM components entails an interesting therapeutic strategy for the treatment of angiogenesis-related diseases. This book chapter is an updated overview of natural compounds with an antiangiogenic effect with the capability to target one or more EMC components.
Keywords: Neovascularización; Angiogénesis; Extracellular matrix; Natural angiogenic compound